2019
DOI: 10.1177/2382120519852046
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Osteopathic Medical Students Regarding Physician Shadowing Experiences Before and During Medical School Training

Abstract: Introduction: Shadowing a physician is an observational experience which includes a student observing a licensed healthcare provider caring for patients. Shadowing is commonly done by students before and during medical school, but little is known about the nature or extent of these extra-curricular observational experiences. Objective: We hypothesized that shadowing experiences were common yet variable. We investigated the prevalence, nature, and perceived value of medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…The significance of early involvement of medical students for clinical practice cannot be overemphasized (16). Preinternship is crucial for medical students and is a rewarding experience (17)(18)(19). Most of students participating in medical pre-internship have little medical knowledge and are curious about the role as a clinician (20).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of early involvement of medical students for clinical practice cannot be overemphasized (16). Preinternship is crucial for medical students and is a rewarding experience (17)(18)(19). Most of students participating in medical pre-internship have little medical knowledge and are curious about the role as a clinician (20).…”
Section: Discussionmentioning
confidence: 99%
“…The large majority of medical students endorse that shadowing experiences before medical school increased their desire to attend medical school. 3,12,13,14 Shadowing experiences can also be gateways for students to develop career mentors and obtain a letter of recommendation for medical school. 3,10,15 This aspect is crucial, especially for those students from disadvantaged backgrounds who may have less connections to the medical field.…”
Section: The Importance Of Shadowingmentioning
confidence: 99%
“…3,12,13,14 Shadowing experiences can also be gateways for students to develop career mentors and obtain a letter of recommendation for medical school. 3,10,15 This aspect is crucial, especially for those students from disadvantaged backgrounds who may have less connections to the medical field. 2,16 New, innovative techniques to enhance shadowing experiences are being developed.…”
Section: The Importance Of Shadowingmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 102 students at a liberal arts college revealed 80.2% of pre-medicine students had experience with shadowing (Adams O'Connell & Gupta, 2006). Langenau et al (2019) found 95.5% of osteopathic medical students reported shadowing a physician as a pre-medical student. It is unclear, however, the percentage of GCs who shadowed a GC prior to entering a graduate program.…”
Section: Introductionmentioning
confidence: 99%